Evolução das taxas de internação hospitalar realizadas pelo SUS em Minas Gerais entre 1998 e 2040 considerando diferenças regionais - Rodrigo Santos Colares (2020)
The objective of the present dissertation is to carry out a projection of demand for hospitalizations for 2040 in the state of Minas Gerais, considering the regional specificities. To do so, analyze regionally the evolution of the age structure and the total hospitalization rates and excluding the chapters of ICD-10 XV (pregnancy, childbirth and the puerperium), XIX and XX (Injuries, poisoning and all external causes). The projections were made for the entire state and for three health macro-regions: Triângulo Norte, Leste do Sul and Nordeste. The projection methods used are: i. deterministic method in order to measure the partial effects of demography on future hospitalization rates and ii. Lee-Carter (1992) stochastic time series method that uses only the history of collection rates that you want to project, considering a three-component projection: the standard, a variation of rates in each age group and its level. The deterministic method estimates hospitalizations from 2019 to 2040 using fixed hospitalization rates in 2018, total and weighted by sex and age. The stochastic method quantifies the uncertainty of the projections through confidence intervals, using the historical series without interruptions applied from 2007 to 2018 of the total hospitalization rates and the rates that do not consider the 3 chapters of the ICD-10. The results show that Minas Gerais experiences the processes of population aging and epidemiological transition in an accelerated and heterogeneous way. These processes are at the most advanced stage in the largest region of the MHDI (Triângulo Norte), in the regions of the medium MHDI (Leste do Sul) and low MHDI (Nordeste). The results of the deterministic projections show the growth of the most accentuated hospitalizations for Minas Gerais and the Triângulo Norte and more conservative for the Leste do Sul region. The Nordeste region presented a reduction of hospitalizations. The Lee-Carter (1992) projection showed growth for all studied regions, and when disregarding the chapters of the ICD-10, this growth was greater for Minas Gerais and for the Leste do Sul and Nordeste macroregions and lower for the Triângulo Norte. The study presents the limitation of not using all variables related to public health services, as well as the limitations of the temporary series used for the projections.